Reverse Ridge Silicon Strip Waveguide and Silica Slot Waveguide Structure for the Dispersion at 1550 nm - Ashok Nandam; Minwan Jung; Yeung Lak Lee; Woojin Shin (IEEE Photonics Journal)
We have proposed a reverse ridge strip waveguide and a slot waveguide structure for the dispersion compensation at 1550 nm wavelength. The resonance between strip- and slot-waveguide modes has been used to calculate the dispersion at the required wavelength. The effective indices of the proposed waveguide structure have been calculated by using the finite difference time-domain (FDTD) method. Our proposed structure shows a high negative dispersion of −1.46 × 105 ps/km-nm over a full width at half maximum (FWHM) of 14 nm at 1552-nm wavelength. The present structure should find applications in the design of integrated-optic dispersion compensators for optical telecommunication and ultrafast waveguide lasers.